DARI KANVAS KE SEJARAH KOTA: STRATEGI, HAMBATAN, DAN FAKTOR PENUNJANG PELUKIS DALAM PENCIPTAAN LUKISAN POTRET WALIKOTA MAKASSAR KOLEKSI MUSEUM KOTA MAKASSAR - Muhammad Suyudi; Muhammad Syafruddin Akmal (FKIP Universitas Khairun, 2026)
This paper is an attempt to analyze portrait paintings of Makassar mayors over time, created by several Makassar artists, currently in the collection of the Makassar City Museum. The research identifies strategies employed by the painters in visualizing mayoral portraits, analyzes inhibiting factors they encountered, and examines supporting factors that can be optimally utilized in the painting process. The research methodology uses a qualitative approach through field observation, in-depth interviews, and documentation. Data collection techniques include interview guides, observation sheets, and documentation studies involving 27 realist painters in Makassar City. The results show that the main strategies of the painters include: multi-source reference studies, utilization of photo restoration technology (Remini and Topaz), and intensive collaboration with subjects’ families and evaluation teams. The most significant inhibiting factors are poor quality reference photos, minimal historical information, and limited working time. Supporting factors include the availability of data from subjects’ families, the painters’ extensive experience, and digital technology support. These findings provide a methodological contribution to the development of realistic portrait art practices based on historical documentation in Indonesia.